Immigration and American Unionism - Briggs, Vernon M. (Book collections on Project MUSE., 2001)
Briggs explores the close relationship between immigration and employment trends beginning in the 1780s. Combining the history of labor and of immigration, he establishes that over time unionism has thrived when the numbers of newcomers have decreased, and faltered when those figures have risen. Briggs argues that the labor movement cannot be revived unless the following steps are taken: immigration levels are reduced, admission categories changed, labor law reformed, and the enforcement of labor protection standards at the worksite enhanced.